2022
DOI: 10.3390/jcm11071971
|View full text |Cite
|
Sign up to set email alerts
|

Balanced Crystalloids versus Normal Saline in Adults with Sepsis: A Comprehensive Systematic Review and Meta-Analysis

Abstract: The crystalloid fluid of choice in sepsis remains debatable. We aimed to perform a comprehensive meta-analysis to compare the effect of balanced crystalloids (BC) vs. normal saline (NS) in adults with sepsis. A systematic search of PubMed, EMBASE, and Web of Sciences databases through 22 January 2022, was performed for studies that compared BC vs. NS in adults with sepsis. Our outcomes included mortality and acute kidney injury (AKI), need for renal replacement therapy (RRT), and ICU length of stay (LOS). Pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
1
14
0
1
Order By: Relevance
“…As described previously at the 12th ADQI conference, the four phases of intravenous fluid therapy -resuscitation, optimization, stabilization and de-escalation -form an appropriate conceptual framework for tailoring fluid therapy to the individual patient context 70 . Although (balanced) crystalloids are often used, the recent BaSICS and PLUS trials and meta-analysis found no clinical benefit of balanced solutions over the use of 0.9% saline solutions [84][85][86][87] . The SMART trial reported that the use of balanced crystalloids significantly decreased major adverse kidney events at day 90 (MAKE 90 ) and a composite end point (death, KRT, or persistent kidney dysfunction) compared saline; however, only ~15% of the patient population had sepsis at baseline 88 .…”
Section: Consensus Statement 3mmentioning
confidence: 99%
“…As described previously at the 12th ADQI conference, the four phases of intravenous fluid therapy -resuscitation, optimization, stabilization and de-escalation -form an appropriate conceptual framework for tailoring fluid therapy to the individual patient context 70 . Although (balanced) crystalloids are often used, the recent BaSICS and PLUS trials and meta-analysis found no clinical benefit of balanced solutions over the use of 0.9% saline solutions [84][85][86][87] . The SMART trial reported that the use of balanced crystalloids significantly decreased major adverse kidney events at day 90 (MAKE 90 ) and a composite end point (death, KRT, or persistent kidney dysfunction) compared saline; however, only ~15% of the patient population had sepsis at baseline 88 .…”
Section: Consensus Statement 3mmentioning
confidence: 99%
“…In patients with AP secondary to hypercalcemia, normal saline should be used instead as ringer’s lactate contains 3 mEq/L calcium. While different guidelines make conflicting recommendations over the choice of crystalloids, normal saline is considered “less physiological” due to high sodium and lack of potassium[ 60 ]. Over-administration of normal saline may also lead to normal anion gap hyperchloremic acidosis in cases of persistent hypotension.…”
Section: Management Of Non-mild Apmentioning
confidence: 99%
“…While other trials specifically evaluating fluid choice in sepsis are ongoing, 24 the totality of the pooled evidence to date still supports a weak recommendation for balanced crystalloids over saline, but it is increasingly clear that, for most patients, the magnitude of the effect is small. 25 The panel noted there was insufficient evidence to make a recommendation on the use of restrictive vs liberal fluid strategies in the first 24 hours of resuscitation in patients with sepsis, and stated that fluids should generally only be given in patients with signs of hypoperfusion. The subsequent publication of the CLASSIC (Conservative vs Liberal Fluid Therapy in Septic Shock) trial, which compared restrictive vs standard IV fluid therapy in patients with septic shock, did not show a difference between these 2 approaches in patient mortality or adverse events up to 90 days.…”
Section: Hemodynamic Management Fluid Managementmentioning
confidence: 99%